Language and Power: A Critical Discourse Analysis of Sexist Expressions in the Novels Re: dan Perempuan - Genvil Darmarris; Ni Wayan Kasni; I Wayan Budiarta (International Journal Labs, 2026)
Sexist language in literary texts often reflects and reinforces unequal gender relations through both explicit and subtle linguistic strategies. In contemporary Indonesian literature, such representations can reveal how gendered power relations and resistance are constructed through narrative language. This study investigates the types of sexist expressions and the construction of gendered power and verbal resistance in the novel Re: dan Perempuan. The research aims to identify how sexist expressions are linguistically realized and how gendered power relations are represented within the narrative. The study employed Sara Mills’ feminist stylistics to classify overt and covert sexism, while Fairclough’s Critical Discourse Analysis is used to examine how linguistic features construct power relations and shape the possibility of verbal resistance. The findings reveal that sexism in the novel is realized through both overt and covert forms. Overt sexism appears through derogatory terms, negative evaluative lexis, and sexist naming practices that directly degrade women’s identity. Meanwhile, covert sexism operates through representational strategies such as backgrounding women’s voices, reinforcing gendered role stereotypes, and foregrounding male authority within narrative structures. These linguistic patterns construct gendered power relations by limiting women’s agency and positioning them within subordinate social roles. Furthermore, verbal resistance is shown to be constrained within the narrative, as women’s voices are frequently mediated through evaluative language, categorization, and emotional internalization rather than direct confrontation. Overall, the study demonstrates that language in the novel functions not only as a medium of storytelling but also as a mechanism through which gender hierarchy is reproduced and negotiated.